Rhetorical characteristics of Vladimir Putin’s speeches at the announcement of military operations in Ukraine - Stanojević, Dobrivoje; Mirkov, Lidija (Sociološki pregled, 2023)
The paper will analyze two speeches of historical importance for international relations and oratory of the 21st century. The first one is the speech of the President of the Russian Federation, Vladimir Putin, of 21 February 2022, which is considered the most significant official announcement of Russia about the events in Ukraine, and the second one is the speech of 24 February 2022 as its logical, meaningful and contextual continuation. Those two speeches, broadcast on multiple channels and media, last for an hour and a half and contain a multitude of material facts exposed through special rhetorical procedures, most often rhetorical examples of misunderstandings. The perspective of the Russian side which could not be seen in the pro-Western media is also given here. It sets up a euphemistic reinterpretation of the events eristically presented in the foreign media as an invasion, an aggression, a war conflict and an attack.